2019
DOI: 10.1123/ijspp.2018-0631
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Anthropometric and Physical Characteristics of Elite Academy Rugby League Players: A Multiclub Study

Abstract: Purpose: To investigate the factors affecting the anthropometric and physical characteristics of elite academy rugby league players. Methods: One hundred ninety-seven elite academy rugby league players (age = 17.3 [1.0] y) from 5 Super League clubs completed measures of anthropometric and physical characteristics during a competitive season. The interaction between and influence of contextual factors on characteristics was assessed using linear mixed modeling. Results: All physical characteristics improved dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…51 The primary objective of pre-season is to develop the physical characteristics of players 52 in preparation for the upcoming season. 10 In addition, pre-season training phase has been found to positively influence changes in body composition 10 and physical qualities 13 in U19 rugby league players. Tactical training volume during in-season (late) was significantly greater than during the pre-season period.…”
Section: Training Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…51 The primary objective of pre-season is to develop the physical characteristics of players 52 in preparation for the upcoming season. 10 In addition, pre-season training phase has been found to positively influence changes in body composition 10 and physical qualities 13 in U19 rugby league players. Tactical training volume during in-season (late) was significantly greater than during the pre-season period.…”
Section: Training Practicesmentioning
confidence: 99%
“…[8][9][10] In order to develop rugby league players for elite competition, understanding the performance and development of physical qualities is essential. There are several studies available that describe the physical qualities of rugby league players, 1,9,[11][12][13] and their associations with match performance. 14 Height and body mass have been found to successfully categorise between playing position and level 1 and positively influence selection between elite and sub-elite categories in under-16 (U16) players.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our results also revealed that incorporating SIT training within the competitive season is feasible without compromising athlete wellbeing or neuromuscular function, and should be consider by practitioners, particularly during the latter stages where some physical characteristics might deteriorate. 3…”
Section: Practical Applicationsmentioning
confidence: 99%
“…1 These characteristics are essential for players to succeed 1 and should be central to rugby league conditioning practices. 2 Developing the physical characteristics of rugby league players is the focus of preseason; 3,4 thereafter emphasis is placed on recovery, technical and tactical development, and match preparations. 5 This change in focus and reduced exposure to maximal-intensity work during training might explain the observed reductions in physical characteristics such as high-intensity intermittent running ability, sprint speed and lower-body power during the latter stages of a ~28-week season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation